2000
DOI: 10.1159/000015476
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of selection and meiotic mechanisms in the production of imbalances in reciprocal translocations

Abstract: We have used data from chromosomally unbalanced offspring observed at birth, as well as data from sperm chromosome analysis, to study the meiotic segregation of reciprocal translocations. Using data from a total of 1,597 unbalanced children, we have observed an excess in maternal origin for all modes of imbalance. This excess is particularly marked for the 3:1 unbalanced mode, for which we have also observed a maternal age effect, indicating a close relationship with autosomal trisomies. In addition, a statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 35 publications
6
42
1
5
Order By: Relevance
“…The first one was that of the preponderance of alternate and adjacent-1 segregations. These two kinds of segregations explained between 58% and 100% of the gametes in over 34 human reciprocal translocations reviewed by Faraut et al [13]. The 83.57% and 90.52% values estimated here were comparable to those reported for numerous human reciprocal translocations.…”
Section: Discussionsupporting
confidence: 82%
“…The first one was that of the preponderance of alternate and adjacent-1 segregations. These two kinds of segregations explained between 58% and 100% of the gametes in over 34 human reciprocal translocations reviewed by Faraut et al [13]. The 83.57% and 90.52% values estimated here were comparable to those reported for numerous human reciprocal translocations.…”
Section: Discussionsupporting
confidence: 82%
“…Analysis of chromosomally unbalanced offspring has shown that: (1) translocations producing adjacent-2 and 3:1 imbalances frequently involve acrocentric chromosomes or chromosome 9 and (2) chromosome 9 is less associated to adjacent-1 imbalances transmitted by men than by women (Faraut et al 2000). Acrocentric chromosome was implicated in translocations described by Estop et al (1998), Van Assche et al (1999) and Geneix et al (2002), while chromosome 9 interested our reciprocal translocation.…”
Section: Discussionmentioning
confidence: 99%
“…This can be visualised by the variable occurrence of asynaptic chromosome regions in the synaptonemic complex [24,25]. It can be assumed that all chromosome abnormalities are generally counter-selected by the meiotic segregation mechanisms [26]. The chromosome abnormalities found in the patientÂŽs lymphocytes need therefore not to be present in his postmeiotic germ cells.…”
Section: Therapeutic Perspectives For Chromo-some Abnormalitiesmentioning
confidence: 99%
“…However, all chromosome abnormalities are generally counter-selected by the meiotic segregation mechanisms [26], and translocation chromosomes are expected with a variable frequency in the postmeiotic germ cells. Robertsonian translocation chromosomes were found with a frequency between 3-27% for an unbalanced karyotype in postmeiotic germ cells by FISH and karyotype sperm analyses [32].…”
Section: Fig (2)mentioning
confidence: 99%